Extreme sports - Dean, Michael, 1949- (Harlow, England : Pearson Education, 2008)
"Up in the air! Down on the ground! Under the water! extreme sports are new, exiting, and dangerous! Learn about extreme sports from aerial ballet to zorbing. Read about the crazy people who love extreme sports. Are extreme sports for you?"--P. [4] of cover
Keywords: Extreme sports; Readers for new literates; High interest-low vocabulary books